2013
DOI: 10.5771/0943-7444-2013-5-295
|View full text |Cite
|
Sign up to set email alerts
|

Research on Automatic Classification of Documents in Library Environment: A Literature Review

Abstract: At present, he is in charge of the library automation and circulation section of Pune University Library. Library automation in general and automated classification in particular are his research interests. He did his doctoral research on development of a semi-automated depth classification scheme for physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Researcher further stated that good quality control vocabulary is required for data collection machine learning-based technology. Automated classification schemes efforts point out: use of natural language and AI in automatic classification; TC; and document classification (Desale and Kumbhar, 2014). Project GERHARD used the Universal Decimal Classification (Toth, 2002), whereas the SCORPION (Online Computer Library Center, 2012) project employed the Dewey Decimal Classification (DDC) to improve the library services automated.…”
Section: Introductionmentioning
confidence: 99%
“…Researcher further stated that good quality control vocabulary is required for data collection machine learning-based technology. Automated classification schemes efforts point out: use of natural language and AI in automatic classification; TC; and document classification (Desale and Kumbhar, 2014). Project GERHARD used the Universal Decimal Classification (Toth, 2002), whereas the SCORPION (Online Computer Library Center, 2012) project employed the Dewey Decimal Classification (DDC) to improve the library services automated.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the results, I found that LISA provided the most relevant results; Google Scholar the greatest quantity; LISTA the highest quality; and LLISR provided only sporadic hits. Finally, I consulted several reading lists and bibliographies that focused on ethical, equitable, or critical cataloging (CritLib.org 2020; University of Cambridge Library 2019; Cook 2020; Snow 2020; Park n.d.), along with the citation lists of previously-conducted reviews (Kazuye Kimura 2018;Williams 1997;Skinner 2014;Gardner 2021;Starr Paiste 2003;Fagan 2010;Desale and Kumbhar 2013;Speller 2007;Homosaurus Editorial Board 2020;Martin 2021;Diao 2018;Sheetija Kathuria 2011;Dunsire 2018;Satija and Martinez-Avila 2017;Velez and Villa-Nicholas 2017;Hudon 2011; In order to properly evaluate the articles, I limited my review and the resulting database to English-language resources. The resulting items (~500) were either collected in full-text digital format, or requested via interlibrary loan.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we consulted several reading lists and bibliographies that focused on ethical, equitable, or critical cataloging (American University. Information Literacy Committee, n.d.; Cook, 2020;CritLib.org, 2020;Snow, 2020;University of Cambridge Library, 2019) along with the citation lists of previously-conducted reviews (Desale and Kumbhar, 2013;Diao, 2018;Dunsire, 2018;Fagan, 2010;Gardner, 2012;Hudon, 2011Hudon, , 2010Kathuria, 2011;Kazuye Kimura, 2018;Martin, 2021;Satija and Martinez-Avila, 2017;Skinner, 2014;Speller, 2007;Starr Paiste, 2003;B.L. Velez, et al, 2013;L.…”
Section: Literature Reviewmentioning
confidence: 99%